Experimental and theoretical spectroscopic studies in relation to molecular structure investigation of para chloro, para fluoro and para nitro maleanilinic acids. (October 2018) - Zayed, M.A.; El-desawy, M.; Eladly, A.A.
Graphical abstract: Graphical correlation between HOMO and LUMO values three derivatives-maleanilic acid molecules calculated at DFT/B3LYP/6-311++G(d, p) level of theory Highlights: This research deals with preparation and structure characterization of three novel maleanilic acid derivatives. Their structures had been characterized by Elemental, FT-IR, Raman XRD and Thermal Analyses. These practical data are compared and confirmed at DFT/B3LYP/6-311++G(d, p) level of theory. Their biological activities and Cytoxicity against cancer cells were performed. Abstract: In the present work novel para chloro, para fluoro and para nitro maleanilic acid derivatives were prepared and investigated using FT-IR, thermal analyses (TA) measurements (TGA/DTG and DTA) in comparison with mass spectral (MS) fragmentation at 70 eV. The crystallographic structures of studied compounds were investigated by X-ray diffraction (XRD). The vibrational frequencies and the corresponding normal modes were evaluated at the optimized geometry. Vibrational modes were analyzed using GAUSSVIEW software. Experimental FT-IR and Raman spectra of the three newly prepared derivatives, namely, (E) – oxo -4- ((4- nitro phenyl) amino)-4- oxobut-2-enoic acid (p-NMA), (E) -4- ((4- chloro phenyl)amino)-4- oxobut -2- enoic acid (p-ClMA), (E) -4- ((4- fluoro phenyl) amino)- 4- oxobut -2- enoic acid (p-FMA) were compared with the theoretically calculated one. FT-IR and the observed vibrational frequencies were assigned; thermal analysis and mass spectrum measurements of the maleanilic acid derivatives were recorded and discussed. The computational calculations were carried out by DFT - B3LYP method with 6-311++G(d, p) basis sets and the corresponding results were tabulated. The alternations of structures of p-FMA, p-ClMA and p-NMA due to the subsequent substitutions were investigated. This correlation between experimental and theoretical calculations provided a good confirmation of the proposed structures of the newly prepared compounds. The derivatives were found to be highly effective against Hepatocellular carcinoma cells > Breast carcinoma cells > colon carcinoma cells. It was recognized, that cancer cells over expression promotes tumorigenic functions; can be suppressed by p-NMA > p-FMA > p-ClMA inhibitors.